Alex Goldiș, Zoom In/ Zoom Out, Cluj-Napoca, Casa Cărții de Știință, 2023, 369 p. - TOHĂTAN, Horațiu (Studia Universitatis Babeș-Bolyai Philologia, 2024)
Alex Goldiș’s 2023 book, ZOOM IN/ ZOOM OUT: Lecturi de critică și literatură contemporană (Readings of contemporary criticism and literature), is a comprehensive and enduring exploration of some of the most influential texts regarding literature and criticism that marked the Romanian literary scene. The book has a tripartite structure, the first part dedicated to Romanian literary fiction and the others to Romanian criticism and international theory respectively. To be more specific, the book represents a collection of reviews and chronicles that span over more than a decade of academic writing. Consequently, the volume is not meant to portray a Romanian canon or a recent literary history, but a more nomadic network of the dynamics concerning contemporary literature and criticism. The first section, dedicated to literary fiction, represents the most extensive fraction of the book. Gathering up thirty-three chapters, this section delves into a diverse exploration of poetry, prose and memoirs.